Book Review: Ingram, N., & Bouchard, C. (Eds.). (2022). Beyond the Great War: Making Peace in a Disordered World. Toronto: University of Toronto Press, 239 p. - Igor K. Bogomolov (Vestnik RUDN. International Relations)
-